Knowledge of breast feeding among primigravida mothers - Mohite, R V; Mohite, V R; Kakade, S V (Bangladesh Journal of Medical Science, 2012)
Background : Breast feeding, the most natural way of infant feeding to satisfy nutritional, metabolic and psychological needs of the baby. Objectives : To assess the knowledge of breast feeding among primi- gravida mothers attending ante-natal clinic and to determine the association between socio-demographic variables with their knowledge. Materials and Methods : Hospital based cross sectional study was conducted at Ante-natal clinic of Krishna Hospital and Medical Research Center, Karad district Satara. Pre-tested structured proforma used to collect information from 590 married primi gravid mothers attending anti-natal clinic during study period by utilizing personal interview method. Statistical Analysis : socio-demographic frequency percentage distribution, knowledge scoreing and statistical association was analysed by using chi-square test. Results: Out of 590 primi gravida mothers,59.66% showed fair quality of knowledge about breast feeding. knowledge about rooming in, family support for breast feeding & burping after breast feeding was 97.7%, 95.4% , 93.5% however weaning, colostrums feed, hazards of bottle feeding and prelactal food was 84%, 82.7%,75.5% and 54% respectively. Statistical association was existed between age, education, religion, socio-economic status & occupation of respondents with their knowledge about breast feeding (?2=151.52, p < 0.0001*; ?2=211.27,p<0.0001*; ?2=133.91,p < 0.0001*; ?2=35.59,p < 0.0001* and ?2=131.04,p<0.0001*) respectively. Conclusion: knowledge of breast feeding among primi gravida mothers attending ANC clinic was of fair in quality. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12603 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12